Strategi Integrated Marketing Communication Produk The Red Ginger Al-Ghozali di Tambak Dalam Baru Surabaya - Nur Faizah; Sokhi Huda (Jurnal Ilmu Komunikasi, 2019)
This study examines the Integrated Marketing Communications (IMC) strategy carried out by Ustadh Al-Ghozali in marketing the red ginger products. IMC strategy plays an important role in the advancement and development of the Home industry. The purpose of this study was to identify the IMC strategy proposed by Al-Ghozali in marketing the red ginger products and to teach this research using a qualitative-descriptive approach with a Marketing Mix theory perspective. The results of this study describe that the IMC strategy carried out by Al-Ghozali includes two stages, namely planning and implementation. In these two stages he employs a strategy of advertising, direct marketing, direct promotion, personal selling, and public relations. The factors that support the success of the IMC strategy are the role of social media and the involvement of resellers. IMC strategy is implemented optimally. Although there are several constrained aspects, there are quite a lot of consumers, especially those in the shop who have collaborated